Pertanggungjawaban Penyelenggara Investasi Bodong yang Memakai Skema Ponzi dengan Modus Investasi Cryptocurrency - Rizki, Fil; Suryokencono, Pramukhtiko (Indonesian Journal of Law and Justice, 2023)
The development of investment is currently very popular so many people are interested in investing to meet their needs, but not many people know about legal and illegal investments, so there are many cases of fraud using investment methods. Usually illegal investments will offer profits and bonuses in recruiting new members. This research aims to determine accountability and sanctions in preventing and taking action against perpetrators of fraudulent investments. The methods used in this research are as follows: statutory approach, case approach, normative juridical research types of primary and secondary legal materials. Data analysis techniques using library legal research. The results of this research show that in the investment business legal entities cannot be held physically responsible but rather the individuals involved in it can be held responsible in accordance with applicable laws. perpetrators of illegal or fraudulent investments in their implementation using new member bonuses violate the rules of criminal law, namely article 105 of Law no. 7 of 2014 concerning Trade.